BUSINESS STRATEGY ARCHITECTURE AT ESQ TOURS - Bramanto Wibisono; Yudha Heryawan Asnawi; Asep Taryana (Pelopor Publikasi Akademika, 2026)
The rapid growth of the Umrah and Hajj industry in Indonesia and globally presents both significant opportunities and competitive challenges for specialized travel organizers. This study examines the business strategy architecture at ESQ Tours (PT Fajrul Ikhsan Wisata), one of Indonesia's leading dedicated Umrah and Hajj travel agencies, established since 2005. The research aims to develop a comprehensive business strategy architecture aligned with the company's vision as a preferred and trusted halal tour operator in Southeast Asia. A qualitative descriptive approach was employed using a case study model, with data collected through direct observation, in-depth interviews, questionnaires, company annual reports, and literature reviews. Data analysis incorporated a multi-layered strategic framework, including foresight analysis, PESTLE, Porter's Five Forces, VRIO, Activity-Based Management (ABM), SWOT, TOWS Matrix, and the A'WOT (AHP-SWOT) method to prioritize strategic choices. The External Factor Evaluation (EFE) matrix yielded a score of 2.860 and the Internal Factor Evaluation (IFE) matrix scored 2.790, placing ESQ Tours in Quadrant V of the IE Matrix, recommending a